2005
DOI: 10.1291/hypres.28.385
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Reduction and Cardiovascular Prevention: An Update Including the 2003-2004 Secondary Prevention Trials

Abstract: In a meta-analysis published in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(149 citation statements)
references
References 150 publications
(226 reference statements)
2
144
1
2
Order By: Relevance
“…Even small gradients in the achieved OBP are known to significantly influence the risk of cardiovascular outcomes [109][110][111][112] and the reduction in OBP translates into a decrease in HBP, although the reduction in HBP is smaller than that of OBP. Based on the observed home-to-office ratios in the BP-lowering effect [103], a decrease in systolic HBP by 2 mmHg may be expected to provide similar relative risk reductions as a decrease in office SBP by 3 mmHg, that is, a 20% reduction in the incidence of stroke.…”
Section: Therapeutic Thresholdsmentioning
confidence: 99%
“…Even small gradients in the achieved OBP are known to significantly influence the risk of cardiovascular outcomes [109][110][111][112] and the reduction in OBP translates into a decrease in HBP, although the reduction in HBP is smaller than that of OBP. Based on the observed home-to-office ratios in the BP-lowering effect [103], a decrease in systolic HBP by 2 mmHg may be expected to provide similar relative risk reductions as a decrease in office SBP by 3 mmHg, that is, a 20% reduction in the incidence of stroke.…”
Section: Therapeutic Thresholdsmentioning
confidence: 99%
“…[1][2][3] A large amount of clinical data has demonstrated that blood pressure (BP) reduction is central to reducing the risk of cardiovascular events. [4][5][6] Consequently, European and American guidelines for the management of hypertension recommend that all individuals should achieve a BP target of o140/90 mm Hg, with a more stringent target of o130/80 mm Hg for patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has recently been demonstrated that the clinical outcome is dependent on the degree of blood pressure reduction rather than on the types of antihypertensive agents used (7). Therefore, the guidelines for the treatment of hypertension (8)(9)(10)(11) state that strict control of blood pressure is essential in order to prevent organ damage and to reduce mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy with multiple agents is also emphasized in the guidelines as a practical way of reducing patients' blood pressure to the desired target levels (8)(9)(10)(11). In fact, combination therapy has already been applied to many cases, because monotherapy is often not sufficiently effective to achieve the target blood pressure.…”
Section: Introductionmentioning
confidence: 99%